Effects of Bariatric Surgery-Related Weight Loss on the Characteristics, Metabolism, and Immunomodulation of Adipose Stromal/Stem Cells in a Follow-Up Study - Amna Adnan; Miia Juntunen; Tuula Tyrväinen; Minna Kelloniemi; Laura Kummola; Reija Autio; Mimmi Patrikoski; Susanna Miettinen (Stem Cells International)
Conclusions: Weight loss improved donors’ metabolic health and partially recovered ASCs’ anti-inflammatory gene expression and cytokine secretion profiles in monocultures. However, it was inadequate to fully restore the immunosuppressive functions of ASCs in cocultures with macrophages. Therefore, not only donor BMI but also weight loss history, among other donor characteristics, might be considered for optimal ASC-based therapy.